Investigating The Influence Of Financial Reward On Lagos State University Staff Turnover Intention - Rasheed Olawale; Ibrahim Olanrewaju (European Scientific Journal, ESJ, 2016)
This study investigated the nature of relationship between turnover intention and financial rewards.Turnover intention can be linked to a situation where motivators are not put in place to get the best out of workers.Simple random sampling techniques was used to select 400 staff (male, n=250, female, n=150) of Lagos State University. A self-administered questionnaire was used to collect data from the participants using Pay Satisfaction Scale (PSS) adapted from the Spector’s Job Satisfaction Scale and the Turnover Intention Scale (TIS) from Mobley, Horner, and Hollingsworth (1978).Pearson’s Product Moment correlation coefficient was used to analyze the data gotten from the participants. One hypothesis was tested and it was found that there is a significant positive relationship between turnover intention and financial rewards.This study recommends that pay satisfaction of workers should be an uttermost concern for the university management so as to reduce staff turnover intentions.